1995
DOI: 10.24266/0738-2898-13.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Cutless and Atrimmec for Controlling Growth of Woody Landscape Plants in Containers

Abstract: Cutless (flurprimidol) effectively reduced shoot elongation of container-grown woody ornamentals, including abelia, cotoneaster, crape myrtle, Foster holly, Mystery gardenia, Manhattan euonymus, photinia and rhododendron. Optimum Cutless 50W (flurprimidol) spray rates were 500–600 ppm for most species except for Manhattan euonymus (1250 ppm), Mystery gardenia and Natchez crape myrtle (750 ppm). Optimum Cutless 0.33G (flurprimidol) granular rates were 0.6 kg/ha (0.5 lb/A) for Coral Beauty cotoneaster and Foster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Thus, it is possible, its application to facilitate the combination of biotechnological and conventional propagation methods, as it takes place in the case of strawberry. For 'Bluecrop' and 'Darrow' cultivars, dikegulac limited shoot elongation, which is a wellknown impact of growth retardants on ericaceous ornamentals [Banko and Stefani 1995, Marosz and Matysiak 2005, Litwińczuk and Prokop 2010. To a certain extent, it might be considered positively as it facilitates nursing more plants at a smaller area.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible, its application to facilitate the combination of biotechnological and conventional propagation methods, as it takes place in the case of strawberry. For 'Bluecrop' and 'Darrow' cultivars, dikegulac limited shoot elongation, which is a wellknown impact of growth retardants on ericaceous ornamentals [Banko and Stefani 1995, Marosz and Matysiak 2005, Litwińczuk and Prokop 2010. To a certain extent, it might be considered positively as it facilitates nursing more plants at a smaller area.…”
Section: Discussionmentioning
confidence: 99%
“…Dikegulac sodium is a plant growth regulator (PGR) that chemically prevents apical dominance by inhibiting cell division in the apical meristem, thereby allowing lateral branching to occur (Arzee et al, 1977;Rezazadeh et al, 2015). Dikegulac sodium has been shown to effectively increase branching of several horticultural crops such as Sedum, Hydrangea, Phlox, and Nepeta (Banko and Stefani, 1995;Cline, 1978;Grossman et al, 2013;Sun et al, 2015). Within 1 d, dikegulac sodium was detected in the apical meristem after being applied to the basal foliage of Chrysanthemum morifolium.…”
mentioning
confidence: 99%
“…Plant growth regulators are synthetic compounds commonly used on ornamental, greenhouse species to produce a uniform and compact appearance (Banko and Stefani, 1995;Krug et al, 2005). Gibberellin [gibberellic acid (GA)] biosynthesis inhibition is the most common mechanism of action used today because it has the least potential for phytotoxicity (Graebe, 1987;Rademacher, 2000).…”
mentioning
confidence: 99%
“…Sold as a granule formulation (Cutless G; SePRO Corp., Carmel, IN), irrigation is required to facilitate the movement of flurprimidol into the root zone of the plant where it is absorbed and translocated through the xylem along with plant water uptake (Sterrett and Tworkoski, 1987). Several studies have shown that flurprimidol has performed as well or better when compared with other landscaping PGRs (Banko and Stefani, 1995;Keever and Gilliam, 1994;Krug et al, 2005;Norcini, 1991).…”
mentioning
confidence: 99%